Zooming-in zooming-out approach - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
An approach to guide especially international research and development organizations to create regionally relevant learning materials that are locally appropriate. This can be applied to any media form.